The effect of sodium chloride on compressibility behaviour of pure kaolinite and natural soil - Nurfathin Izzati , Mohd Azhar (2012)
Clayey materials are often used as liner material in landfills. In some cases, natural soils containing clay minerals are used as cheaper alternatives. The Seawater intrusion in landfill located nearby coastal area might affect the stability and performance of clay liner system located at the bottom of the landfill. The effect of the seawater to the compressibility of the clay liner is still not well understood. This study focused on the effects of saltwater on the plasticity as well as the compressibility characteristics of a natural soil (KB soil) and commercially available FM-C kaolin. Double-oedometer tests were employed by applying increasing vertical stress on initially saturated slurried specimens. The specimens were allowed to inundate under 0.5 M sodium chloride (NaCl) solution. Both the plasticity and the compressibility behavior of FM-C kaolin and KB soils were affected by NaCl solutions. A much higher water contents and void ratios were attained by FM-C kaolin as compared to KB soil, primarily due to the amount of clay fractions available. However, the differences were found to be minimal. Based on the findings of this study, the use of natural soil may be useful in replac \ ing commercially available kaolinite as cost effective alternatives material in landfill liner systems.